2022
DOI: 10.1002/cbm.2255
|View full text |Cite
|
Sign up to set email alerts
|

Social, health and ethnicity correlates of complaints of excessive police force

Abstract: Background: Following several high-profile police shootings of Black Americans, renewed debate has focused on race as a predictor of police violence. Past research has been inconsistent on this score. Some scholars argue that socioeconomic issues are better predictors of police-related violence than are race and ethnicity.Aims: To test relationships between complaints of excessive use of police violence and racial/ethnic population demographics, allowing for social and mental health variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…As a consequence, the police tend to be more active in poor neighbourhoods, leading to more interactions between police officers and residents; such interactions may escalate into violence between civilians and police (Sorensen et al, 1993). Previous evidence has found that community level mental-health strain, in particular, is associated with police misconduct (Smith et al, 2022).…”
Section: Shootings By Police Officersmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the police tend to be more active in poor neighbourhoods, leading to more interactions between police officers and residents; such interactions may escalate into violence between civilians and police (Sorensen et al, 1993). Previous evidence has found that community level mental-health strain, in particular, is associated with police misconduct (Smith et al, 2022).…”
Section: Shootings By Police Officersmentioning
confidence: 99%
“…Although Black individuals make up somewhere between 11% and 15% of the population of the USA, they are over a quarter (27.5%) of victims in police‐involved fatal shootings in 2018 (Siegel et al., 2019); Beck (2021) reports that a similar higher proportion of violent criminal arrests are recorded against Black people, suggesting that the extent of police contact may be a key issue. At present, there are mixed findings on whether race does or does not predict police shootings or other misconduct (Cesario et al., 2019; Hemenway et al., 2020; Scott et al., 2017; Smith et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Disproportionately high levels of police violence among people identified as Black and Latine (Edwards et al, 2019; Scott et al, 2017) have significant health consequences for these populations (Jindal et al, 2022; McLeod et al, 2019). Over the past decade, public awareness of police violence have been on the rise through media coverage of several high‐profile events such as the killings of Breonna Taylor and George Floyd (Smith et al, 2022). The most well‐known of these movements–Black Lives Matter (BLM)–is largely centered around promoting policy change, moving toward investment in the future of Black people, with a major emphasis on transforming the juvenile and criminal legal systems.…”
Section: Introductionmentioning
confidence: 99%
“…While mental illness was only attributed to one out every 42 fatal assaults on police officers in the United States between 1993 and 2002 (Cordner, 2006), PwMI die in approximately one of every four fatal police interactions (Saleh et al, 2018) and are 16 times more likely to be killed in a police encounter than the general population (Fuller et al, 2015). When police officers perceive PwMI as a threat and have limited or no training on how to peacefully defuse these types of crises, they may resort to undue force, or in other cases, “mercy bookings” in order to maintain the safety of themselves and/or others (Smith et al, 2022). This greatly contributes to the critical issue that PwMI represent a disproportionately large fraction of the jail and prison populations (Bronson and Berzofsky, 2017).…”
mentioning
confidence: 99%